Being survivors: therapeutic communication for people living with HIV/AIDS (plwha) - Effendy, Chairil; de Vera, Rosemarie Virginia M.; Asfar, Dedy Ari; Syahrani, Agus; GS, Achmad Daeng (Jurnal Studi Komunikasi, 2021)
The number of People Living With HIV/AIDS (PLWHA) is steadily increasing. HIV/AIDS is caused by a virus that infects the body and weakens the immune system, making it difficult to fight germs, viruses, fungi, and other pathogens. HIV and AIDS are still considered taboo diseases that should not be openly discussed. People living with HIV/AIDS (PLWHA) are discouraged from seeking treatment due to stigma and discrimination. Eliminating stigma and discrimination against people living with HIV/AIDS will improve the process of preventing and overcoming HIV/AIDS cases. In addition, therapeutic communication also affects interpersonal relationships. This research aims to figure out how the therapeutic communication efforts of People living with HIV/AIDS (PLWHA) become survivors. The method used in this research is phenomenology, where the informants in this study are people with HIV/AIDS who live in Surabaya. This study concludes that therapeutic communication efforts to People living with HIV/AIDS (PLWHA) are by presenting volunteers who help people living with HIV/AIDS (PLWHA) based on the same fate as People living with HIV/AIDS (PLWHA). The presence of volunteers (PLWHA) assists and bridges the gap between patients and therapy, fostering a sense of comfort for PLWHA. They also make other patients feel more at ease while they are receiving treatment in the hospital.